Going Remote: Faculty Educational Initiatives on Building Community During COVID-19 Through Online Teaching - Bice, Matthew; Hollman, Angela; Vail, David; Vu, Phu (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2020)
The novel COVID-19 pandemic, with its global impact, has fundamentally altered the way in which universities function. The current manuscript presents four educational initiatives, including experiences and practices of faculty members at a mid-sized Great Plains university. From the perspective of three different academic colleges and popular research programs, this paper explores how a difficult situation was approached as an opportunity to face challenges yet still provide students a high-quality educational experience. This paper is applicable to faculty, staff, and administrators at institutions of higher education as they explore innovative pedagogical approaches.